APPLICATIVE CONSTRUCTIONS IN JAVANESE - Sofwan, Ahmad (Language Circle: Journal of Language and Literature, 2010)
Applicative constructions refer to those in which an underlying indirect object or oblique is realised as a coreargument. The applied argument replaces P and in most languages becomes the direct object. In mostinstances, the verb usually bears a distinctive inflection expressing the semantic relation borne by the directobject. In Javanese applicative constructions could be intransitive-based and transitive-based, and theyinvolve oblique to 2 advancement or 3-2 advancement. The N- prefix on the verb, the deletion ofpreposition, and the suffix Ã¢â¬âi/ni or Ã¢â¬âake mark the advancement to direct object. The suffix Ã¢â¬âi/ni is used tomark locative, recipient and destination advancement, whereas the suffix Ã¢â¬âake is used to mark benefactiveand instrumental advancement. It is also possible that advancement to direct object is not marked with anysuffix.